An economic impact of incorrect referrals for MRI and CT scans: A retrospective analysis. Issue 3 (13th March 2023) - Baiguissova, Dinara; Laghi, Andrea; Rakhimbekova, Assel; Fakhradiyev, Ildar; Mukhamejanova, Aigerim; Battalova, Galina; Tanabayeva, Shynar; Zharmenov, Samat; Saliev, Timur; Kausova, Galina
Abstract: Background and Aims: Up to date, no research on the economic efficacy of diagnostic modalities, such as magnetic resonance imaging (MRI) and computerized tomography (CT), has been done in Central Asia. The aim of this study was to analyse the inappropriate appointments of MRI and CT scanning procedures in Kazakhstan. Methods: We used the imaging diagnostic reports and medical records from 9725 planned outpatient CT and MRI exams performed in two major hospitals in Almaty. The study period was for the period 2014–2019. The independent experts‐radiologists evaluated the MRI and CT exams for validity using the ACR® compliance standards and RCR recommendations. Results: The results showed that the combined costs of MRI and CT scans increased by 17.982 between 2014 (22.537) and 2019 (40.519), p = 0.002. The highest rate of MRI examinations was observed in 2019, with a rate of 6.9 per 10, 000 people. It was determined that in 2019 the highest rate for men who undertook CT was equal to 12.4 per 10, 000 people, while for women it was equivalent to 5.7 per 10, 000 patients. The majority of non‐corresponding imaging examinations ( n = 1304) were referred for MRI and CT scans by general practitioners. We detected the irrational referrals for head and neck radiological examinations in n = 178 (13.7%) cases, and the abdominal cavity checks in n = 249 (19.1%) cases ( p = 0.001). The main portion of erroneously unreasonable referrals for examination of the abdominal organs was made by surgeons in n = 43 (3.3%) cases. Conclusion: The findings indicated an increase in the number of referrals for unnecessary CT and MRI tests over the research period (2014–2019). It had a substantial impact on the rise in healthcare system expenses. The results demonstrate the need for the education of GPs and improving the approaches for diagnostics.